Feed the Future Bangladesh 2018/2019: Zone of influence endline assessment (April 2013 – December 2020) - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
Feed the Future seeks to sustainably reduce global poverty, hunger, and malnutrition by helping partner countries boost agriculture-led growth, resilience, and nutrition. Program efforts are designed to impact the population in Zones of Influence (ZOI) in Feed the Future target countries. Progress in achieving Feed the Future’s objectives is tracked using population-based performance indicators collected at baseline then periodically thereafter. The International Food Policy Research Institute (IFPRI) produced this report for the United States Agency for International Development (USAID) Bureau for Resilience and Food Security (RFS), USAID/Bangladesh, the Government of Bangladesh, and development partners. The report compares indicator estimates and select demographic and household characteristics from the 2018/2019 ZOI Survey, which serves as the Feed the Future Phase One endline survey, with the baseline assessment conducted in 2011/2012 in Bangladesh. This report only includes the Feed the Future Phase One indicators. Secondary data sources are used when needed or appropriate. The Feed the Future Phase One ZOI in Bangladesh includes mostly rural areas in 20 districts consisting of 120 upazilas (sub-districts) in three divisions in the south and southwest region of the country. This assessment provides information about progress on Feed the Future Phase One ZOI indicators. The assessment is designed to show changes in key indicator estimates from the Feed the Future Phase One baseline assessment to the endline assessment. The Feed the Future ZOI Survey endline assessment, however, was not designed to support conclusions of causality or program attribution.